ANALISIS FAKTOR YANG MEMPENGARUHI PEMBERIAN ASUHAN KEBIDANAN KEHAMILAN HOLISTIK DI LAYANAN BIDAN KOMUNITAS - Ika, Ika Lustiani; Rahmayani, Rahmayani (Jurnal Medikes (Media Informasi Kesehatan), 2024)
All Indonesian citizens have the right to receive health services. “Health” refers to physical, mental, social and spiritual health (Health Law No. 17, 2023). This state is called holistic health. Holistic midwifery care has become an important part of midwifery practice today. The emergence of holistic midwives in maternity care in the Netherlands is a relatively new development. The first Dutch holistic midwife started her current practice around 2000. It took several years for a second holistic midwife to join her, but by the beginning of the next decade there were already more than a dozen midwives, and current estimates (2019) range between 20 and 30 holistic midwives which is active in the Netherlands (Hollander, 2019). Holistic therapy methods that can be applied in Indonesia in midwifery care include body and mind intervention (prenatal yoga), alternative medical service systems (acupressure, aromatherapy), manual healing methods, pharmacological & biological treatment (herbal therapy in midwifery practice), diet and nutrition, and so on (Minister of Health Regulation, 2018). The holistic midwifery service model for pregnant women can be integrated into the 10 T midwifery service standards in the interview aspect (Decree of the Minister of Health, 2020). The aim of this research is to determine the factors that influence the provision of holistic pregnancy midwifery care in community midwife services in Curug District, Serang City. The method used was bivariate chi-square and multivariate analysis using logistic regression with a total sample of 27 midwives. The research results show that there is a statistically significant relationship between knowledge with a P-Value of 0.000 (<0.05), attitude with a P-Value of 0.002 (<0.05), motivation with a P-Value of 0.023 (<0.05), and training with a P-Value of 0.000 (<0.05) on the provision of holistic pregnancy midwifery care in community midwifery services. Statistically there is no significant relationship between midwife practice place and P-Value 0.168 (>0.05), length of service with P-Value 0.286 (>0.05), education with P-Value 0.154 (>0.05), and age with a P-Value of 0.244 (>0.05) on the provision of holistic pregnancy midwifery care in community midwifery services. The variable that has the greatest relationship to the provision of holistic pregnancy midwifery care in community midwifery services in Curug District, Serang City is knowledge with logistic regression 86,456.